2004
DOI: 10.1016/j.neuroimage.2004.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Less white matter concentration in autism: 2D voxel-based morphometry

Abstract: Autism is a neurodevelopmental disorder affecting behavioral and social cognition, but there is little understanding about the link between the functional deficit and its underlying neuroanatomy. We applied a 2D version of voxel-based morphometry (VBM) in differentiating the white matter concentration of the corpus callosum for the group of 16 high functioning autistic and 12 normal subjects. Using the white matter density as an index for neural connectivity, autism is shown to exhibit less white matter concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 36 publications
5
94
0
6
Order By: Relevance
“…It is possible that the behavioral phenotype of low social approach [8,49] and failure to modify behavioral patterns in the hole-board familiarization assay might be related to the overt neuroanatomical defects in these mice, including absent corpus callosum and reductions in the hippocampal commissure [82]. Some studies have reported deficiencies in corpus callosum volume or white matter concentration in autistic patients [1,13,41,61,81,83].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the behavioral phenotype of low social approach [8,49] and failure to modify behavioral patterns in the hole-board familiarization assay might be related to the overt neuroanatomical defects in these mice, including absent corpus callosum and reductions in the hippocampal commissure [82]. Some studies have reported deficiencies in corpus callosum volume or white matter concentration in autistic patients [1,13,41,61,81,83].…”
Section: Discussionmentioning
confidence: 99%
“…Here we applied tensor-based morphometry (TBM; see Davatzikos et al, 1996;Thompson et al, 2000;Chung et al, 2001Chung et al, , 2003Chung et al, , 2004Fox et al, 2001;Shen and Davatzikos, 2003;Studholme et al, 2001Studholme et al, , 2003Teipel et al, 2004, for related work) to detect and automatically quantify the subtle and distributed patterns of brain atrophy in HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…The CC is the largest fiber bundle connecting the left and the right cerebral hemispheres in the hu man brain. Since the higher cognitive functions of the brain are highly affected by the impaired communication between the hemi spheres, several studies [5][6][7][8][9][10] have proposed to analyze the CC for autistic subjects. In [5][6][7], the CC had been traced from the midsagittal MRI slice.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical difference analysis was applied to find out which part in the CC contributes significantly to iden tification of autistic brains. Chung et al [8] applied a voxel based morphometry approach using a freely available public domain soft ware package (i.e., SPM software-http;llwww.jil.ion.ucl.ac.uklspml) to spatially normalize the midsagittal MRI slice to a common stereo tactic space in order to segment the CC and localize the CC subre gions that are related to autism. To cover more CC anatomy, stud ies [9,10] account not only for the midsagittal slice but also for four adjacent slices on both sides.…”
Section: Introductionmentioning
confidence: 99%